Medical treatment of cholestatic liver diseases: From pathobiology to pharmacological targets - Paumgartner, Gustav (Baishideng Publishing Group Co., Limited, 2006)
Bile secretion is dependent on the coordinated functions of a number of hepatobiliary transport systems. Cholestasis may be caused by an impairment of bile secretion, an obstruction of bile flow or a combination of the two. The common consequence of all forms of cholestasis is retention of bile acids and other potentially toxic compounds in the hepatocytes leading to apoptosis or necrosis of hepatocytes and eventually to chronic cholestatic liver disease. In certain cholestatic disorders there is also leakage of bile acids into the peribiliary space causing portal inflammation and fibrosis. The following pharmacological targets for treatment of intrahepatic cholestasis can be identified: stimulation of orthograde biliary secretion and retrograde secretion of bile acids and other toxic cholephils into the systemic circulation for excretion via the kidneys to reduce their retention in the hepatocytes; stimulation of the metabolism of hydrophobic bile acids and other toxic compounds to more hydrophilic, less toxic metabolites; protection of injured cholangiocytes against toxic effects of bile; inhibition of apoptosis caused by elevated levels of cytotoxic bile acids; inhibition of fibrosis caused by leakage of bile acids into the peribiliary space. The clinical results of ursodeoxcholic acid therapy of primary biliary cirrhosis may be regarded as the first success of this strategy.